The Influence of Information Asymmetry on Earnings Management With Good Corporate Governance (GCG) as the Moderating variable - Hartika Prawidaningrum Harahap (STIE Perbanas Surabaya, 2017)
The purpose of this study is to test and find the influence of information asymmetry on earnings management with good corporate governance as moderating variable in banking sector companies listed on the Indonesia Stock Exchange (IDX)) in 20102014. Earnings management variable was measured using the approach of Beaver and Engel (1996), information asymmetry variable was measured using the approach of bid-ask spread, and good corporate governance (GCG) variable was measured using GCG self-assessment. The research type used was quantitative research using secondary data. The population in this study was all banking sector companies listed on the IDX in 2010-2014. The number of samples was 15 banking companies taken from the total of 41 banking companies. Sampling technique was conducted using documentation. Methods of analysis used in this study were simple linear regression analysis and moderated regression analysis. The results of this study show that information asymmetry has a significant influence on earnings management, and GCG moderates the influence of information asymmetry on earnings management.